Non-Human Agency and Experiential Faith among Diné Oodlání, "Navajo Believers" - Jenkins Marshall, Kimberley (Anthropologica, 2015)
The neo-Pentecostal Oodlâni movement is on the rise among Diné (Navajo) of the US South-West, characterized by independent Navajo-led churches and charismatic worship. In this article, I focus on the experiential nature of neo-Pente costalism to argue that its growth, over and above other forms of Navajo Christianity, capitalizes on a type of resonant rupture with traditional Navajo spirituality. Specifically, I focus on the Oodlâni relationship with non-human (supernatural) actors. While experientiality provides an avenue for deeply felt continuity, a close look at Oodlâni non-human actors (and the options for interacting with them) demonstrates that neoPentecostalism fundamentally forges cultural rupture.